Sexual Role and History of Sexual Transmitted Infection as a Risk of HIV Seroconversion among Men who have Sex with Men who Attended Bali Medika Clinic Badung, Bali - Ni Putu Diwyami; Anak Agung Sagung Sawitri; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: HIV prevalence among men who have sex with men (MSM) increased from 5% on 2007 into 12% on 2011 in Indonesia. High risk sex behaviour was reported associated with HIV seroconversion, however reported research publication about risk factors of HIV seroconvertion among MSM is limited in Indonesia. This study aims to investigate risk factors of HIV seroconversion among MSM. Methods: Case control study was conducted based on cohort data of MSM who repeatedly visited Bali Medika Clinic, Kuta, Badung, Bali Province between 2011-2015. HIV Seroconversion was defined as MSM with a negative HIV status at the beginning of the observation and became positive on the next visit. Data were analyzed using Kaplan Meier and logistic regression method. Results: Median time of HIV seroconversion among MSM was 458 days or 1.2 years (IQR=224-699). Multivariate analysis showed that risk factors of HIV seroconversion were repeated STD’s experience in the last 6 months with AOR=8.33 (95%CI: 1.77-89.81); had 1 time STD’s history in last 6 months with AOR=1.91 (95%CI: 1.15-3.83); receptive sexual relationship in the last 6 months with AOR=3,45 (95%CI: 1.68-7.11); and versatile sexual relationship in the last 6 months with AOR=2.37 (95%CI: 1.09-5.13). Conclusion: STD’s experience, receptive and versatile sexual role are risk factors of HIV seroconversion among MSM.